CRISPR/Cas Enzyme Catalysis in Liquid–Liquid Phase‐Separated Systems - Yaqin Zhang; Jianai Chen; Zhina Wu; Chenfei Zhao; Rui Wang; Zhiping Li; Jiasi Wang; Di Wang (Advanced Science)
Abstract The clustered regularly interspaced palindromic repeats (CRISPR) /CRISPR‐associated proteins (Cas) system is the immune system in bacteria and archaea and has been extensively applied as a critical tool in bioengineering. Investigation of the mechanisms of catalysis of CRISPR/Cas systems in intracellular environments is essential for understanding the underlying catalytic mechanisms and advancing CRISPR‐based technologies. Here, the catalysis mechanisms of CRISPR/Cas systems are investigated in an aqueous two‐phase system (ATPS) comprising PEG and dextran, which simulated the intracellular environment. The findings revealed that nucleic acids and proteins tended to be distributed in the dextran‐rich phase. The results demonstrated that the cis‐cleavage activity of Cas12a is enhanced in the ATPS, while its trans‐cleavage activity is suppressed, and this finding is further validated using Cas13a. Further analysis by increasing the concentration of the DNA reporter revealed that this phenomenon is not attributed to the slow diffusion of the reporter, and explained why Cas12a and Cas13a do not randomly cleave nucleic acids in the intracellular compartment. The study provides novel insights into the catalytic mechanisms of CRISPR/Cas systems under physiological conditions and may contribute to the development of CRISPR‐based molecular biological tools.